IMPLEMENTASI PEMANFAATAN POJOK BACA DALAM MENINGKATKAN LITERASI MEMBACA DI SEKOLAH DASAR - Isra Muhammad Nur Ichwana; Talita Pohan (STKIP Subang, 2024)
This research discusses the reading corner in the implementation of the school literacy movement. In the current era, reading activities may seem very boring. Students need to be motivated to learn, and having a book corner available in the classroom can provide them with the opportunity to read. This applies to both elementary schools and madrasah ibtidaiyah, based on theoretical studies. The data obtained are from references about reading corners and the school literacy movement. The results of the theoretical study in this research indicate the existence of a reading corner that stimulates students' interest. Having a reading corner helps students appreciate their time more, gain more knowledge, and builds students' interest. Furthermore, it aims to instill noble character traits in students because the more they read, the smarter they become, which in turn leads to academic success.